The Interrelationship among Language Use, Linguistic Competence, and Higher Order Skills - Hazim Taisir Dayij Alkhrisheh; Failasofah Failasofah; Taisir Alkhrisheh (Universitas Jambi, Indonesia, 2021)
This research aims to investigate the relationship amongst three concepts: language use, linguistic competence, and critical thinking. Pedagogical and cognitive aspects of language learning are evident in the implications of this research concerning how thought influences learning, and how learning influences thought. The sample of the study consisted of 52 students from Mutah University in Jordan who are enrolled in the BA program in the department of English language and literature. The instruments used in the study included the LEAP-Q to measure the multilingual level of participants to determine language use, a critical thinking test to measure the participants’ level of reasoning, and a TOEFL proficiency test to measure the participants’ level of linguistic competence. The findings show significant positive correlations between language use and critical thinking, between linguistic competence and critical thinking, and between language use and linguistic competence. We conclude that language use enhances the linguistic abilities and possibly enhances the cognitive capabilities of the participants. We recommend encouraging students to use the second language inside and outside the classroom to enhance their linguistic and cognitive abilities.